Heat transfer and efficiency of dual channel PVT air collector: a review - Fudholi, Ahmad; Zohri, Muhammad; Taslim, Ivan; Aliyah, Fitrotun; Gani Koto, Arthur (Institute of Advanced Engineering and Science, 2019)
Solar energy is free, renewable and environment friendly and has been widely used in electricity generation and thermal energy through photovoltaic thermal (PVT) system. A PVT collector is a combination of a PV panel and a thermal collector in a single unit to simultaneously generate electricity and thermal energy. In this review, mathematical models for dual channel PVT air collectors is presented. This review presents various research and development, as well as heat transfer and thermal modelling of dual channel PVT air collectors. Moreover, various mathematical models that evaluate the performances base on energy and exergy analysis of dual channel PVT air collectors are presented. Energy balance is the basic concept in developing the mathematical models. Generally, steady-state one-dimensional linear first-order differential equations were reported for solution of mathematical model. Energy and exergy efficiencies of dual channel PVT air collectors were 22.5%–67% and 3.9%-58%, respectively.